The Need for Building Science Education: A Review - Joseph Laquatra (Techniques and Innovation in Engineering Research Vol. 6, 2022)
The purpose of this paper is to review the history of what has come to be known as building science and its importance to the residential construction industry. This research uses a review and summary method to provide a historical context for building science and its definition. Improvements in building science education are required as the demand for high-performance housing rises. Learning how to avoid issues, such as water intrusion and mould growth, in the construction of energy-efficient housing has traditionally been done through trial and error. These problems have been addressed by building codes in prescriptive, non-evidence-based ways. Motivating current housing industry professionals to learn through continuing education is a start, but the core issue must be addressed by incorporating building science education into curricula related to architecture, engineering, construction management, and other fields.Further monitoring of the creation of building science curricula in 4-year university programmes in construction management and related fields at community colleges. Additionally, metrics should be created to gauge the success of this effort, such as decreases in the frequency of residential construction failures and levels of building science comprehension among general contractors and subtrade workers.